Творчо-організаційна складова вокальної підготовки студентів-акторів (на прикладі ХДАК) - Єрошенко, Олена Віталіївна (ХДАК, 2018)
Розглянуто сучасні засоби творчо-організаційної складової вокального навчання студентів-акторів, визначено її особливості (на прикладі ХДАК). Відзначені праці, присвячені проблематиці вокального навчання акторів драматичного й музично-драматичного театрів загалом. Наголошено на значному використанні музичного матеріалу в сучасних театральних постановках, що, відповідно, потребує професійної музично-вокальної підготовки акторів. Аналізуються творчо-дидактичні зв’язки курсів «Музично-драматичний клас» і «Основи вокалу» як складових комплексної дисципліни «Основи вокального виконавства і теорії музики».

The paper emphasizes the significant use of music material in modern theatrical performances that, accordingly, requires an appropriate music and vocal training of actors.The perspective of vocal training of future actors contains the issues concerning creative and organizational component of the training process in higher educational institutions. The characteristic feature of training the students majoring in «Performing arts of drama theater and cinema» at the Theatre Faculty of the Kharkiv State Academy of Culture is a modern innovative approach to dealing with the vocal and stage training that consists in the introduction of the new music and drama field of study (i.e., the course «Musical and Drama Class»). The author traces the main factors of the vocal and stage training of the future actors of Drama Theater and Cinema, analyzes the creative and didactic connections of the courses «Music and Drama Class» and “Fundamentals of Vocals” as components of the integrated discipline «Fundamentals of Vocal Performance and Music Theory». This creative and organizational innovation in the field of vocal training guides the students-actors to the gradual acquisition of thorough skills and abilities in vocal and drama area, according to modern performing art and cinematography requirements.
Keywords: вокальна підготовка акторів; театральна освіта; vocal training; student-actor